SYNTHESIS, CHARACTERIZATION AND EVALUATION OF STARCH XANTHATE AS A SUPERDISINTEGRANT IN THE FORMULATION OF FAST DISSOLVING TABLETS - KUMAR, R. SANTOSH; SATYA YAGNESH, T. NAGA (International Journal of Applied Pharmaceutics, 2018)
Objective: To synthesize, characterize and evaluate starch xanthate as a superdisintegrant in the formulation of fast dissolving tablets by employing 23 factorial design. Methods: Starch xanthate was synthesized by gelatinization process. The physical and micromeritic properties were performed to evaluate the synthesized starch xanthate. The fast dissolving tablet of ibuprofen was prepared by employing starch xanthate as a superdisintegrant in different proportions in each case by direct compression method using 23 factorial design. The drug content, hardness, friability, disintegration time and other dissolution characteristics like percent dissolved in 5 min (PD5), dissolution efficiency in 5 min (DE5%) and first order rate constant (K1) were used in the evaluation of prepared fast dissolving tablets. Results: The starch xanthate prepared was found to be fine, free flowing slightly crystalline powder. Starch xanthate exhibited good swelling in water. The study between ibuprofen and starch xanthate was shown the absence of interaction by fourier transform infrared spectra (FTIR) and differential scanning calorimetry (DSC). The drug content (100±5%), hardness (3.6–4 kg/sq. cm), and friability (0.12-0.15%) has been effective with regard to all the formulated fast dissolving tablets employing starch xanthate. The disintegration time of all the formulated tablets was found to be in the range of 12±0.01 to 312±0.02s. The optimized formulation F5 has the least disintegration time i.e., 12±0.01s. The In vitro wetting time of the formulated tablets was found to be in the range of 76±0.21 to 217±0.17s. The In vitro wetting time was less (i.e., 90s) in optimized formulation F5. The water absorption ratio of the formulated tablets was found to be in the range of 16±0.16 to 174±0.21%. The cumulative drug dissolved in the optimized formulation F5 was found to be 99.83±0.56% in 5 min. Conclusion: The dissolution efficiency of ibuprofen was enhanced when starch xanthate was found to be a superdisintegrant when combined with sodium starch glycolate, croscarmellose sodium and, hence it could be used in the formulation of fast dissolving tablets to provide immediate release of the contained drug within 5 min.